Propose a conceptual framework for the cloud ERP adoption among Malaysian SMEs - Albachay, Arif Razzaq Obaid; Asmai, Siti Azirah; Zainal Abidin, Zaheera; Ali, Mohanad Faeq; Mohammed Al-Khazraji, Ali Abdul-Jabbar; Talib, Mohammed Saad (Taylor's University, 2021)
The SMEs sector is undergoing a significant transition towards cloud enterprise resource planning systems. These systems have proved to be effective for organizations by providing advantages such as organizing and managing data remotely, accepting the pay-as-you-go approach, and enhancing relevant information via a cloud computing platform. It also offers more characteristics such as information technology agility and scalability, business processes enhancement and competitiveness enhancement. This makes the cloud ERP system essential to the sustainability of SMEs. However, the adoption rate of the ERP cloud between SMEs has been reported as a little low compared to other information systems such as ERP. To address this gap, we developed a conceptual framework for understanding the intentions of SMEs towards the adoption of the cloud ERP and investigating the comprehensive factors that impact or impede the adoption of the cloud ERP. A framework focused on the theories of technology, organization, environment framework (TOE), diffusion of innovation theory (DOI), Iacouvo model, critical mass theory (CMT). Therefore, this structure is intended to help SMEs managers understand and improve their predictive potential for cloud ERP adoption. The framework was built using three dimensions: technology, organization, and environment. The proposed framework would be a vital lens for decision-makers on the cloud ERP adoption and will be aware of their intentions.